The Implementation of Load Balancing Using Per Connection Classifier Method Using Mikrotik RB1100 - Siagian, Pedro Maldini; Hari Aspriyono; Eko Prasetiyo Rohmawan (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2023)
The Implementation of Load Balancing Using Per Connection Classifier Method Using Mikrotik RB1100 By : Pedro Maldini Siagian 1) Hari Aspriyono 2) Eko Prasetiyo Rohmawan 2) Poltekkes Kemenkes Bengkulu as a university which has 2.000 students and 250 employees, has internet access through 2 providers, namely Icon Dedicated and Icon Broadband. Even though it has 2 internet lines, the distribution of internet line that is evenly distributed still cannot be implemented. Load Balancing carried out on Mikrotik RB1100 at Poltekkes Kemenkes Bengkulu can help distribute internet traffic evenly, and can overcome lost connections due to backing up broken connections with available connections. Load Balancing used Per Connection Classifier is a method that will send a set of packets over several existing links, taking into original account of packets. In this method, packets coming from one communication session will be routed through only one link. Through QoS (Quality of Service) testing that the result was that load balancing carried out was running well and as expected Poltekkes Kemenkes Bengkulu which can evenly distribute the connection traffic used. Keywords : Load Balancing, Per Connection Classifier, Mikrotik RB1100, Poltekkes Kemenkes Bengkulu Infomation: 1) Student 2) Supervisors